(untitled) (Training and Practice : Journal of Educational Sciences, 2016)
Kindergarten teacher students of our college take part in external kindergarten practice each year, as an organic addition to their theoretical college training. This year also several students joined the so called Bird Song Kindergarten program. In the framework of this program they worked out and implemented an independent program with kindergarten children as part and parcel of their research activity. As a follow-up to one of such programs in the form of a two-week project the introduction of the birds living around the kindergarten was in the focus, through Experimental Education Programs. The process of complex cognition included: walk, the creation of artificial nesting places (hangouts) and their continuous monitoring, handicraft, drama pedagogy games, voice recording, bird feeding (preparation of suet balls), etc. I introduce in my article the two-week project and the effects it had on children.